Thermoneutral housing shapes hepatic inflammation and damage in mouse models of non-alcoholic fatty liver disease - Oates, Jarren R.; Sawada, Keisuke; Giles, Daniel A.; Alarcon, Pablo C.; Damen, Michelle S.M.A.; Szabo, Sara; Stankiewicz, Traci E.; Moreno-Fernandez, Maria E.; Divanovic, Senad (Frontiers in Immunology, 2023)
Inflammation is a common unifying factor in experimental models of non-alcoholic fatty liver disease (NAFLD) progression. Recent evidence suggests that housing temperature-driven alterations in hepatic inflammation correlate with exacerbated hepatic steatosis, development of fibrosis, and hepatocellular damage in a model of high fat diet-driven NAFLD. However, the congruency of these findings across other, frequently employed, experimental mouse models of NAFLD has not been studied. Here, we examined the impact of housing temperature on steatosis, hepatocellular damage, hepatic inflammation, and fibrosis in NASH diet, methionine and choline deficient diet, and western diet + carbon tetrachloride experimental models of NAFLD in C57BL/6 mice. Key differences relevant to NAFLD pathology uncovered by thermoneutral housing include: (i) augmented NASH diet-driven hepatic immune cell accrual, exacerbated serum alanine transaminase levels and increased liver tissue damage as determined by NAFLD activity score; (ii) augmented methionine choline deficient diet-driven hepatic immune cell accrual and increased liver tissue damage as indicated by amplified hepatocellular ballooning, lobular inflammation, fibrosis and overall NAFLD activity score; and (iii) dampened western diet + carbon tetrachloride driven hepatic immune cell accrual and serum alanine aminotransferase levels but similar NAFLD activity score. Collectively, our findings demonstrate that thermoneutral housing has broad but divergent effects on hepatic immune cell inflammation and hepatocellular damage across existing experimental NAFLD models in mice. These insights may serve as a foundation for future mechanistic interrogations focused on immune cell function in shaping NAFLD progression.